2005
DOI: 10.1590/s1519-566x2005000500018
|View full text |Cite
|
Sign up to set email alerts
|

Atividade larvicida de óleos essenciais contra Aedes aegypti L. (Diptera: Culicidae)

Abstract: -In the search for alternative chemical control against Aedes aegypti L., many researches are developed and encouraged in order to find new insecticidal plant substances. In this work, the larvicidal effect of ten essential oils was tested on A. aegypti. The oils were extracted by steam distillation and their chemical composition determined by GL-chromatography coupled with mass spectroscopy. The essential oils were diluted in aqueous solutions of dimethyl sulfoxide with concentrations of: 100, 50, 10, and 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
19

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 9 publications
4
31
0
19
Order By: Relevance
“…As this work, the inseticidal activity of L. sidoides was reported by Furtado et al (2005) against A. aegypti, which was effective to kill the larvae. Botelho et al (2007) found that essential oil of L. sidoides from Northeast Brazil has as major components thymol and carvacrol and Cavalcanti et al (2004) also verified that this compound are toxic against A. aegypti larvae.…”
Section: Chemical Constitution Of Essential Oilmentioning
confidence: 69%
“…As this work, the inseticidal activity of L. sidoides was reported by Furtado et al (2005) against A. aegypti, which was effective to kill the larvae. Botelho et al (2007) found that essential oil of L. sidoides from Northeast Brazil has as major components thymol and carvacrol and Cavalcanti et al (2004) also verified that this compound are toxic against A. aegypti larvae.…”
Section: Chemical Constitution Of Essential Oilmentioning
confidence: 69%
“…Citrus limonia Osbeck, popularly known as "limão", has a major compound in its essential oil limonene. The essential oil of C. limonia has larvicidal activity on Aedes aegypti L. (Furtado et al, 2005). Citrus fruits are known to contain natural antioxidants in oil, pulp, seed and bark.…”
Section: Plants Used In Screening and Their Pharmacological Activitiesmentioning
confidence: 99%
“…O óleo essencial de L. sidoides geralmente possui como constituinte principal o timol (Fontenelle et al, 2007). Diversos trabalhos demonstram seus efeitos antibacteriano (Botelho et al, 2007), fungicida (Fontenelle et al, 2007;Silva et al, 2011), larvicida (Furtado et al, 2005;Souza et al, 2011) e antimicrobiano (Silva et al, 2008). Já a espécie C. citratus produz um óleo essencial rico em citral, sendo que estudos têm atribuído atividades biológicas para o mesmo, tais como: inseticida (Lima et al, 2008), antimicrobiana (Santos et al, 2009), antibacteriano (Pereira et al, 2004), antifúngica (Guimarães et al, 2011) A extração dos óleos essenciais foi realizada pelo método de hidrodestilação utilizando-se aparelho de Clevenger modificado.…”
Section: Introductionunclassified